Perception Policies for Intelligent Virtual Agents - Souza De Freitas, Giancarlo; Gelaim, Thiago Ângelo; Rodrigues Pires De Mello, Rodrigo; Azambuja Silveira, Ricardo (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2019)
Agents deployed to dynamic environments, such as virtual and augmented reality,  need specific mechanisms to capture relevant features from the environment. These mechanisms enable agents to avoid process some useless information and act quickly. The primary goal of this work is to investigate the perception policies of an agent situated in a virtual environment. Perception policies allow giving more priority to sensors perceiving the changes occurring in the environment. Based on the proposed model, each sensor follows a strategy that can change its priority in the overall system. We developed two policies to change the sensors prioritization. The performance evaluation of the proposed model consists of comparing both approaches in a highly dynamic environment.